Review: Etnotaksonomi dan bioekologi tumbuhan pasak bumi (Eurycoma longifolia Jack.) - Hidayati, Syafitri; Zuhud, Ervizal A.M.; Adiyaksa, Ivan Khofian; Al Manar, Primadhika (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2021)
Eurycoma longifolia (EL) is a species that have economical benefit as medicinal ingredients for human health. This species grows in tropical forest areas with high rainfall. Research on the ecology of EL has been done a lot, but research related to ethnotaxonomic, bioecology that includes morphology, ecology, and the association of EL with other plants hasn’t been done much. This study aim to analyze the bioecology of EL plant. The method is literature study, which is looking for literature on the results of research that has been carried out related to EL. The results showed that EL has long been known by the communities of Indonesia and other countries in Southeast Asia with several local names. This plant is also associated with other plants around where it grows, one of which is kempas (Koompassia malaccensis). Based on the results of literature review, research on natural regeneration of EL hasn’t been done much. Therefore, there is a need for research related to the natural regeneration of EL. In addition, it is necessary to conduct research related to the characteristics of the place to grow for optimal cultivation of EL. Thus, the preservation of EL in the future can be maintained.